Numerical calculation of the transverse vibrations of the multispan beams for moving load - Tho, Do Xuan; Khang, Nguyen Van (Vietnam Journal of Mechanics, 1992)
In this paper the numerical calculation of the transverse vibrations of the Multiplan beams for moving load is considered. A program has been worked out for the numerical integration of the motion equations on IBM-PC AT or XT. This program is useful in calculating the vibrations of the suspension bridges.